If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) + 4 = 17 Reorder the terms: 3(-1 + 2x) + 4 = 17 (-1 * 3 + 2x * 3) + 4 = 17 (-3 + 6x) + 4 = 17 Reorder the terms: -3 + 4 + 6x = 17 Combine like terms: -3 + 4 = 1 1 + 6x = 17 Solving 1 + 6x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6x = 17 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = 17 + -1 6x = 17 + -1 Combine like terms: 17 + -1 = 16 6x = 16 Divide each side by '6'. x = 2.666666667 Simplifying x = 2.666666667
| 6x-x^2=32-12x+x^2 | | 7x+y=-25 | | y=12-5x | | (a+3)-4=-2 | | 8x-1=23+4x | | p-1=9+p | | 9=3x-10 | | (6a-2)(5a^2+a-4)= | | 2w+3wx=x+2 | | Z+27=14 | | -2(a+4)=16 | | 7x=5+4x | | (4+x)=3x | | 12-3a=2a+2 | | 2x+49=6x+9 | | 7x=5+4 | | 1.3x+64.2=2.7x+12.82 | | 7x+10y=19 | | -4(a-2)=16 | | 15x^2=4x | | 3(a-2)=-3a+12 | | v^2=18-3v | | -21-7x=-126 | | 8=4x+2 | | (v+7)(v-9)= | | -2a+4=4a-2 | | r^2=-24-11r | | 12-(2x+8)=(x-16) | | x^2-22x+21= | | 2a^2+11ab-63b^2= | | 12a^2+20ab-25b^2= | | y=-2x^2+4x-7 |